1992
DOI: 10.2176/nmc.32.342
|View full text |Cite
|
Sign up to set email alerts
|

Ruptured Cerebral Aneurysm Associated with Coarctation of the Aorta —Report of Two Cases—

Abstract: Two cases of ruptured cerebral aneurysm associated with coarctation of the aorta are presented. The aneurysms were successfully clipped in the acute stage prior to correction of the coarctation. Ruptured aneurysm should be treated as early as possible, and unruptured aneurysm should also be treated before aortic repair, if the general condition of the patient allows.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 7 publications
0
17
0
1
Order By: Relevance
“…In prior CHD case reports, intracranial aneurysms or the presenting CVA are mostly described in patients with CoA, and sometimes in patients with cyanotic CHD, such as truncus arteriosus, transposition of great arteries. [8][9][10][11][12][13][22][23][24] The embryological basis for such association between CoA (or other CHD) and intracranial aneurysm remains unclear. Besides, we also found that age was a risk factor for CVA in the whole CHD cohort.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In prior CHD case reports, intracranial aneurysms or the presenting CVA are mostly described in patients with CoA, and sometimes in patients with cyanotic CHD, such as truncus arteriosus, transposition of great arteries. [8][9][10][11][12][13][22][23][24] The embryological basis for such association between CoA (or other CHD) and intracranial aneurysm remains unclear. Besides, we also found that age was a risk factor for CVA in the whole CHD cohort.…”
Section: Discussionmentioning
confidence: 99%
“…8 CoA patients may even present with aneurysmal cerebral or subarachnoid hemorrhage. [11][12][13] Given all these findings, we may suggest that hypertension in CoA patients, who have systemic arteriopathy, further increases the risk of CVA and should be aggressively controlled.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We used advanced monitoring techniques to titrate blood pressure to a cardio-, kidney-, and neuro-protective level. Aortic stenosis rarely remains asymptomatic until adulthood and is associated with aneurysmal rupture early in life (mean, 25 years) [1,3,5]. Compared to the general population, patients with AC have a higher bleeding rate and more commonly develop multiple cerebral aneurysms [4,10].…”
Section: Discussionmentioning
confidence: 99%
“…In patients with intracranial aneurysms, the incidence is estimated to range from 0.19 to 1.9% [1][2][3]. With an 4.8% incidence of aneurysm rupture as a cause of death, spontaneous SAH is far more common when compared to the general population [4].…”
Section: Introductionmentioning
confidence: 99%